Convicting With Reasonable Doubt: An Evidentiary Theory of Criminal Law - Teichman, Doron (2018)
This Article presents an evidentiary theory of substantive criminal law according to which sanctions are distributed in proportion to the strength of the evidence mounted against the defendant. It highlights the potential advantages associated with grading penalties in proportion to the probability of wrongdoing and situates this claim within both consequentialist and deontological theories of punishment. Building on this analysis, the Article reviews the doctrinal tools used to achieve the goal of evidentiary grading of sanctions and shows that key factors in criminal law are geared towards dealing with evidentiary uncertainty. Finally, the Article explores the underlying logic of the evidentiary structure of criminal law and argues that this structure can be justified on psychological, economic, and expressive grounds